(untitled) (Research, Society and Development, 2020)
In 2015, the Fundão dam broke and destroyed rural communities in Mariana-MG. The reparation for the affected communities in Mariana was defined in the Public Civil Action, which establishes Family Resettlement as one of the means of reparation for the violation of the right to housing. Our goal is to compare the data of rural properties affected witch the reparation parameters. Data from the affected rural properties were compared with the repair parameters, revealing that 65.7% of the 102 rural properties affected by mining waste have less than the Mariana Fiscal Module, 20 ha, a minimum size for the rural properties to be considered economically viable. To ensure the economic viability of new properties, reparations parameters must be determined. We recommend compensation by adding a Fiscal Module to the destination area and implementing agreements and guidelines for redress through the draft National Policy on the Rights of Populations Affected by Dams.